Distributional Pattern of Avifauna Species in Different Habitat Types in Ardo-kola and Yorro Local Government Areas, Taraba State, Nigeria - Peter Andrew Awai; Noku Suzan Saviour (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study seeks to determine and compare avifauna distribution in Ardo-kola and Yorro local Government area of Taraba State. The habitats were divided into Open Habitat, Montane Forest and Plantation Habitat. Point count method was used to collect data on avifauna distribution. 11,772 avifauna species from 37 families and 65 species were recorded. High avifauna distribution was observed both in wet and dry seasons in Plantation habitat. Plantation habitat can serve as a refuge for avifauna species, hence, there is needs for conservation attention by the local authorities and Locals